Selenium Nanoparticles Biosynthesized by Pantoea agglomerans and Their Effects on Cellular and Physiological Parameters in the Rainbow Trout Oncorhynchus mykiss - Francisco Yanez-Lemus; Rubén Moraga; Luis Mercado; Carlos Jara-Gutierrez; Carlos T. Smith; Paulina Aguayo; Kimberly Sanchez-Alonzo; Apolinaria García-Cancino; Ariel Valenzuela; Victor L. Campos (Biology, 2022)
The applications of nanoparticles (Nps) as food additives, health enhancers, and antimicrobials in animal production are increasing. The aim of this study was to evaluate the effect of selenium (Se) nanoparticles (Se0Nps) stabilized with L-cysteine (Se0Nps/L-Cys), as a nutritional supplement, on immunological, oxidative status, and productive parameters in O. mykiss. TEM and SEM-EDS showed the accumulation of spherical Se0Nps entirely composed by elemental selenium (Se0) as intracellular and extracellular deposits in Pantoea agglomerans UC-32 strain. The in vitro antioxidant capacity of Se0Nps/L-Cys was significant more efficient ROS scavengers than Se0Nps and Na2SeO3. We also evaluate the effect of Se0Nps/L-Cys on cell viability and oxidative stress in RTgill-W1, RTS-11, or T-PHKM Oncorhynchus mykiss cell lines. Se0Nps/L-Cys showed less toxic and high antioxidant activity than Se0Nps and Na2SeO3. Finally, the dietary Se0Nps/L-Cys had a significant better effect on both plasma lysozyme and respiratory burst activity (innate immune response), on tissular Gpx activity (oxidative status), and on well-being (productive parameter) of O. mykiss when it is compared to Se0Nps and Na2SeO3. Se0Nps/L-Cys is a promising alternative for nutritional supplement for O. mykiss with better performance than Na2SeO3 and Se0Nps, ease to implementation, and reduced environmental impact.